Assessment of the challenges encountered by aquaculture business in Cabanatuan City, Nueva Ecija, Philippines - M. Bautista, Alvin Gino (Asian Journal of Agriculture and Rural Development, 2025)
The study aimed to identify and assess the challenges encountered by aquaculture farmers in Cabanatuan City, Nueva Ecija, Philippines, across the three critical phases of production: pre-operation, operation, and post-harvest, including marketing and sales. Using a descriptive-quantitative research design, the study gathered data from selected aquaculture farmers through structured questionnaires, supported by site visits and direct observations to validate responses. The results revealed that aquaculture farmers face moderate challenges, particularly in accessing capital, preparing aquaculture facilities, obtaining technical knowledge, and dealing with unreliable suppliers. Additional concerns include vulnerability to extreme weather conditions, inconsistent government support, and limited access to modern technology. Based on the findings, the study concluded that addressing these constraints is crucial to improving the productivity, resilience, and sustainability of aquaculture operations in the city. The study recommended enhancing government-led extension services, including farmer training, technical support, and policy interventions, to strengthen the aquaculture value chain. Moreover, partnerships with private stakeholders and academic institutions were suggested to bridge technical gaps. The study aligns with Sustainable Development Goal 14: Life Below Water, by promoting responsible aquaculture practices that contribute to food security, economic development, and environmental protection. Future research may explore the role of cooperatives and digital tools in mitigating these challenges.